"A red cross appeared in the sky" and other celestial signs: Presumable European aurorae in the mid AD 770s were halo displays. Issue 10 (10th December 2015) - Neuhäuser, D. L.; Neuhäuser, R.
Abstract: The interpretation of the strong 14 C variation around AD 775 as one (or several) solar super‐flare(s) by, e.g., Usoskin et al. (2013) is based on alleged aurora sightings in the mid AD 770s in Europe: A red cross / crucifix in AD 773/4/6 from the Anglo‐Saxon Chronicle, inflamed shields in AD 776 (both listed in the aurora catalogue of Link 1962), and riders on white horses in AD 773 (newly proposed as aurora in Usoskin et al. 2013), the two latter from the Royal Frankish Annals. We discuss the reports about these three sightings in detail here. We can show that all three can be interpreted convincingly as halo displays: The red cross or crucifix is formed by the horizontal arc and a vertical pillar of light (either with the Sun during sunset or with the moon after sunset); the inflamed shields and the riders on white horses were both two mock suns, especially the latter narrated in form of a Christian adaptation of the antique dioscuri motive . While the latter event took place early in AD 774 (dated AD 773 in Usoskin et al. 2013), the two other sightings have tobe dated AD 776, i.e. anyway too late for being in connection with a 14 C rise that started before AD 775. We also sketch the ideological background of those sightings and there were many similar reports throughout that time. In addition, we present a small drawing of a lunar halo display with horizontal arc and vertical pillar forming a cross for shortly later, namely AD 806 June 4, the night of full moon, also from the Anglo‐Saxon Chronicle; we also show historic observations of halo phenomena (mock suns and crosses) from G. Kirch and Hevelius – and a modern photograph. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)